2009
DOI: 10.5194/bgd-6-2267-2009
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Calcification, a physiological process to be considered in the context of the whole organism

Abstract: Abstract. Marine organisms that produce calcium carbonate structures are predicted to be most vulnerable to a decline in oceanic pH (ocean acidification) based on the understanding that calcification rates will decrease as a result of changes in the seawater carbonate chemistry thereby reducing carbonate ion concentration (and associated saturation states). Coastal seas are critical components of the global carbon cycle yet little research has been conducted on acidification impacts on coastal benthic organism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
47
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 34 publications
(50 reference statements)
5
47
0
1
Order By: Relevance
“…Counter-intuitive results are also found: several studies have shown increased calcification rates under reduced pH (Wood et al, 2008;Findlay et al, 2009). This has been attributed to up-regulation of calcification rates at the expense of other physiological processes, such as metabolic rates (Findlay et al, 2009).…”
Section: Cause-effectsupporting
confidence: 56%
See 1 more Smart Citation
“…Counter-intuitive results are also found: several studies have shown increased calcification rates under reduced pH (Wood et al, 2008;Findlay et al, 2009). This has been attributed to up-regulation of calcification rates at the expense of other physiological processes, such as metabolic rates (Findlay et al, 2009).…”
Section: Cause-effectsupporting
confidence: 56%
“…This has been attributed to up-regulation of calcification rates at the expense of other physiological processes, such as metabolic rates (Findlay et al, 2009). Also, ocean acidification has been shown to positively affect carbon fixation rates in some calcifying photosynthetic organisms (Kroeker et al, 2010;Pandolfi et al, 2011;Ries et al, 2009).…”
Section: Cause-effectmentioning
confidence: 99%
“…Since calcification is an energy-demanding process (Palmer, 1992), the impaired aerobic metabolism under hypoxia could be the underlying mechanism causing the reduced calcification as previously observed (e.g. Cheung et al, 2008;Findlay et al, 2009;Wijgerde et al, 2014).…”
mentioning
confidence: 86%
“…It has been suggested that carbonate saturation state does not necessarily influence calcification since calcifying organisms may be able to use bicarbonate ions for this process (Ries, 2011a;Bach, 2015). Instead, growing evidence reveals that calcification is mainly driven by the energy metabolism of calcifying organisms since this process is energy-dependent (Findlay et al, 2009;Wijgerde et al, 2014).…”
mentioning
confidence: 99%